2020
DOI: 10.1101/2020.09.03.281576
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pathogenic Mutations in the Kinesin-3 Motor KIF1A Diminish Force Generation and Movement Through Allosteric Mechanisms

Abstract: The kinesin-3 motor KIF1A functions in neurons where its fast and superprocessive motility is thought to be critical for long-distance transport. However, little is known about the force-generating properties of kinesin-3 motors. Using optical tweezers, we demonstrate that KIF1A and its C. elegans homolog UNC-104 undergo force-dependent detachments at ~3 pN and then rapidly reattach to the microtubule to resume motion, resulting in a sawtooth pattern of clustered force generation events that is unique among th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(51 citation statements)
references
References 93 publications
9
42
0
Order By: Relevance
“…WT KIF1A and mutant motors were expressed in E. coli bacteria. Our recent work has shown that the velocity and force generation properties of KIF1A expressed in E. coli bacteria and mammalian cells are statistically indistinguishable 57 . A similar construct has also been used in other studies 51,58,59 .…”
Section: Resultsmentioning
confidence: 97%
“…WT KIF1A and mutant motors were expressed in E. coli bacteria. Our recent work has shown that the velocity and force generation properties of KIF1A expressed in E. coli bacteria and mammalian cells are statistically indistinguishable 57 . A similar construct has also been used in other studies 51,58,59 .…”
Section: Resultsmentioning
confidence: 97%
“…Our recent work has shown that the velocity and force-generation properties of KIF1A expressed in E. coli bacteria and mammalian cells are statistically indistinguishable. 55 A similar construct has also been used in other studies. 49 , 56 , 57 …”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that introduction of the human KIF1A gene into unc-104(e1265) background results in restoration of movement to near WT levels (14), indicating that the human gene can largely compensate for unc-104's cellular functions in worms. Indeed, single-molecule studies with recombinant proteins show that UNC104 and KIF1A have similar motile and force-generation properties (30).…”
Section: A Genetic Model Reveals Kif1a P305l Behaves As a Null Mutatimentioning
confidence: 99%
“…To assess any effects on force generation, we performed single-molecule optical tweezers assays (7,39,40) with our human KIF1A proteins. In a parallel study (30), we have shown that full-length rat KIF1A and tail-truncated rat KIF1A (1-393)-LZ both detach at an average load of ~2.7 pN and then rapidly reattach to the MT to resume motion, resulting in a sawtooth-like force-generation pattern in which forcegeneration events cluster tightly together (30). We find that human KIF1A (1-393-LZ), which differs from a similar rat KIF1A construct by a single amino acid (valine instead of an isoleucine at residue 359), also exhibits a sawtooth-like force-generation pattern (Fig.…”
Section: The P305l Mutation Impairs Kif1a's Ability To Generate Forcementioning
confidence: 99%